Pendidikan Multikultural dalam Diskursus Islam - Norvaizi, Ikhrom; Lestari, Nopita; Nurlaili, Nurlaili; Karni, Asniti (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research focuses on understanding the relationship or relevance between multicultural education and Islam. Likewise, this research aims to explore and understand the relevance of the values and principles of multicultural education to Islam. This research also emphasizes that multicultural education harmonises with Islamic values and principles. This research was conducted using a qualitative approach, namely descriptive research emphasising analysis. The methodology of this research is a literature study. Multicultural education in Islam aims to create intelligent, religious, creative, educated individuals and accept society's diversity. Multicultural values are Islamic values, including tauhid, ummah, rahmah, musawah, tasamuh, tadhamun, ta'awun and kinship. Multicultural principles in Islam include pluralism, equality, and modesty in diversity. The relationship between Islamic beliefs and multicultural education is discussed in this article. Multicultural education shares many principles and characteristics with Islam and is closely related. Multicultural education is the basis for all educational components to foster an atmosphere of openness, tolerance, and mutual respect and develop students' character so they are ready to solve problems that arise in a pluralistic society.